Composition-Interpretation-Improvisation Processes in XO pt. II by Dino Rešidbegović: Comparative Analysis of two Interpretations - Hanan Hadžajlić (INSAM)
The composition XO pt. II for flute with processors, amplified cello, amplified piano and analog sound synthesizers, by Dino Rešidbegović, was published in 2016 as an electroacoustic adaptation of its previous version, XO for undetermined instrumentation. The phenomenon of the notation of both versions, presented through the graphic score, comes from the very idea of/about the composition. The score is divided into nine squares which form a network with incorporated abstract shapes of different colors. In the middle of the score is a chart of a spectral analysis of the composition The Impact of the Analog Synthesizer for ensemble, also by Rešidbegović. The only difference between the scores of the two versions is the instrumental parameters table involved in XO pt. II for three performers. The main task of this paper is primarily the analysis and comparison of two interpretations of XO pt. II by the same three performers, with a difference in duration of almost 19 minutes. The goal is to reconstruct and explicate the improvisation as a potential basis for a compositional-technical analysis. A composition-interpretation-improvisation processes chain represents the main structure of the general process which forms the composition XO pt.II, involving composer and performers – interpreted as equal, interdependent creators of the musical work.